THE STUDY OF STRUCTURE AND LINGUISTIC RULES IN WRITING OBSERVATION RESULTS OF REPORT TEXT AT SENIOR HIGH SCHOOL - Nisa Fadillah Kaffah; Euis Eti Rohaeti; Dede Abdurrakhman (JLER (Journal of Language Education Research), 2021)
In the 2013 curriculum, Indonesian language lessons are text based, thus, students are required to understand various types of texts, one of which is the text of the observation report.This study analyzes the text of the observation report applied as teaching material. The aim of this study is to produce a description of the structure and rules data in the text of the observation report and use it as teaching material, describing the structure and language rules of the text of the observation report in class X in SMAN 1 Majalaya. The author used a qualitative descriptive method by documentation techniques. Analysis of this data finished by assessing the students' writing one by one based on the assessment criteria of each aspect. The results showed that the ability of students of SMAN 1 Majalaya to write report texts from observations of class X MIPA (Science class) 1 and 2 was categorized quite capable. The aspects studied were the structure and language norms of the text of the observation report including conjunction between sentences and coordinative conjunction. The ability of students to apply the text structure of the report of observations includes general definitions, section descriptions, the definition of benefits categorized as capable, because there are only 11 texts out of 30 texts that do not have an observation report structure. Whereas in the language rules of the text the results of observations include conjunctions between sentences and coordinative conjunctions categorized as able because only 22 texts do not have the rules of linguistic conjunctions between sentences.